Microscopic Properties of Capacitor Insulating Oil under External Electric Field Based on Density Functional Theory - Meijuan Shi; Zhiyi Pang; Yi Li; Rui Qin (International Journal of Polymer Science)
Due to its high flash point, low viscosity, high solubility, low poor point, strong coloration ability, and high voltage resistance, 1-phenyl-1-xylylethane (PXE) is widely utilized as an electrical insulation oil. In this study, density functional theory is employed to apply an electric field within the molecule for calculating the molecular structure and spatial charge characteristics of PXE under external electric fields. The alterations in molecular structure, reaction activity, and insulation properties of PXE when subjected to external electric fields are analyzed correspondingly. As the external electric field gradually increases, the potential energy of the molecule elevates leading to a decrease in stability of the molecular chain. Under conditions of high electric field intensity, the molecule experiences enhanced polarity and polarization, leading to alterations in the chemical bonds within the benzene ring and ultimately resulting in structural degradation. The space charge characteristics further demonstrate a gradual decrease in the energy gap of PXE molecule, accompanied by an enhancement in molecular conductivity under the influence of an external electric field. Meanwhile, the HOMO and LUMO orbitals exhibit a gradual localization towards the two termini of the molecular chain, and the active sites of PXE molecular chain underwent alterations, resulting in both ends of the chain exhibiting electrophilic and nucleophilic reactivity. The variation in trap energy levels at different depths results in the distortion of local field strength within the PXE. The absorption peak in the high frequency region of the molecular infrared spectrum exhibits a noticeable redshift, while the absorption peak in the low frequency region experiences a blue shift. The research findings can establish a theoretical framework for the micromorphology analysis of electric aging insulation oil in power capacitors, thereby offering a reference point for determining the breakdown voltage value in macroscopic electrical breakdown experiments. Additionally, these results provide valuable insights into material optimization and modification strategies.